Strong indication of an extinction‐based saturation of the flora on the Pacific Robinson Crusoe Islands. Issue 5 (1st February 2018) - Greimler, Josef; Schulze, Christian H.; López Sepúlveda, Patricio; Novoa, Patricio; Gatica, Alejandro; Reiter, Karl; Wessely, Johannes; Baeza, Carlos; Peñailillo, Patricio; Ruiz, Eduardo; Stuessy, Tod
Abstract: Oceanic islands are vulnerable ecosystems and their flora has been under pressure since the arrival of the first humans. Human activities and both deliberately and inadvertently introduced biota have had and continue to have a severe impact on island endemic plants. The number of alien plants has increased nearly linearly on many islands, perhaps resulting in extinction‐based saturation of island floras. Here, we provide evidence for such a scenario in Alejandro Selkirk, Robinson Crusoe Islands (Archipelago Juan Fernández, Chile). We compared species richness and species composition of historical vegetation samples from 1917 with recent ones from 2011. Changes in species' relative occurrence frequency were related to their taxonomic affiliation, dispersal mode, distribution status, and humidity and temperature preferences. While total species richness of vascular plants remained relatively similar, species composition changed significantly. Plants endemic to the Robinson Crusoe Islands declined, exotic species increased substantially within the period of ca. 100 years. Further, the relative occurrence frequency of plants with preferences for very warm and humid climate decreased, while the opposite was found for plants preferring drier and colder environments. Potential drivers responsible for this dramatic shift in the vegetation within only one century might have been the large goat population affecting especially small populations of endemic plants and climatic changes. Taking into account a substantial extinction debt, we expect further shifts in the vegetation of this small oceanic island toward alien plants. This would have significant negative consequences on global biodiversity, considering that island floras contribute substantially to global plant species richness due to their high proportion of endemics. Abstract : On the island Alejandro Selkirk (Robinson Crusoe Islands), plant species composition changed significantly although species richness remained similar. Endemic plants declined, and exotic species increased substantially within the period of ca. 100 years.